Immunobiotic Strains Modulate Toll-Like Receptor 3 Agonist Induced Innate Antiviral Immune Response in Human Intestinal Epithelial Cells by Modulating IFN Regulatory Factor 3 and NF-κB Signaling - Kanmani, Paulraj; Kim, Hojun (Frontiers in Immunology, 2019)
Many studies have demonstrated that immunobiotics with immunoregulatory functions improve the outcomes of several bacterial and viral infections by modulating the mucosal immune system. However, the precise mechanisms underlying the immunoregulatory and antiviral activities of immunobiotics have not yet been elucidated in detail. The present study was conducted to determine whether selected lactic acid bacteria (LAB) modulate toll-like receptor 3 (TLR3) agonist polyinosinic:polycytidylic acid (PolyI:C) induced viral response in human intestinal epithelial cells. PolyI:C increased the expression of interferon- β (IFN-β), interleukin-6 (IL-6), interleukin-8 (IL-8), monocyte chemoattractant protein (MCP-1), and interleukin-1 β (IL-1β) in HCT116 cells, and these up-regulations were significantly altered when cells were pre-stimulated with LAB isolated from Korean fermented foods. LAB strains were capable to up-regulate IFN-β but down-regulated IL-6, IL-8, MCP-1 and IL-1β mRNA levels as compared with PolyI: C. HCT-116 cell treatment with LABs beneficially modulated the mRNA levels of C-X-C motif chemokine 10 (CXCL-10), 2-5A oligoadenylate synthetase 1 (OSA1), myxovirus resistance protein (MxA), TLR3, and retinoic acid inducible gene-I (RIG-I) and TLR negative regulators. In addition, LABs increased IFN-β, IFN-α and interleukin-10 (IL-10) and decreased tumor necrosis factor-α (TNF-α) and IL-1β protein/mRNA levels in THP-1 cells. LABs also protected the cells by maintaining tight-junction proteins (zonula occludens-1 and occludin). The beneficial effects of these LABs were mediated via modulation of the interferon regulatory factor 3 (IRF3) and nuclear factor-kappa B (NF-κB) pathways. Overall, the results of this study indicate that immunobiotics have potent antiviral and anti-inflammatory activities that may use as antiviral substitutes for human and animal applications.